Augmenting Sensor Performance with Machine Learning Towards Smart Wearable Sensing Electronic Systems. (21st April 2022) - Zhang, Songlin; Suresh, Lakshmi; Yang, Jiachen; Zhang, Xueping; Tan, Swee Ching
Abstract : Wearable Sensing Electronic Systems By implementing machine learning algorithms, the performance of smart wearable sensing electronic systems is significantly improved, with a boosted capability to collect and analyze physiological data from the human bodies (i.e., biochemical, biopotential, and biophysical signals), thus enabling a pyramid of applications, such as health monitoring, disease diagnosis and treatment, human‐machine interfaces, and virtual/augmented reality, etc. More information can be found in article number 2100194 by Swee Ching Tan and co‐workers.